2014
DOI: 10.1037/a0035880
|View full text |Cite
|
Sign up to set email alerts
|

Free to punish: A motivated account of free will belief.

Abstract: Belief in free will is a pervasive phenomenon that has important consequences for prosocial actions and punitive judgments, but little research has investigated why free will beliefs are so widespread. Across 5 studies using experimental, survey, and archival data and multiple measures of free will belief, we tested the hypothesis that a key factor promoting belief in free will is a fundamental desire to hold others morally responsible for their wrongful behaviors. In Study 1, participants reported greater bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
147
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(173 citation statements)
references
References 87 publications
19
147
2
1
Order By: Relevance
“…This research has uncovered many exciting results and has shown that people's intuitions about whether free will is possible in a deterministic universe are mixed and vary depending on various contextual and motivational factors (e.g., Clark, Luguri, Ditto, & Knobe, 2014;Deery, Davis, & Carey, 2015;Nadelhoffer, Shepard, Nahmias, Sripada, & Ross, 2014;Nichols, 2011;Nichols & Knobe, 2007;Paulhus & Carey, 2011;Pizarro & Helzer, 2010; see also Cushman & Young, 2009). This research has uncovered many exciting results and has shown that people's intuitions about whether free will is possible in a deterministic universe are mixed and vary depending on various contextual and motivational factors (e.g., Clark, Luguri, Ditto, & Knobe, 2014;Deery, Davis, & Carey, 2015;Nadelhoffer, Shepard, Nahmias, Sripada, & Ross, 2014;Nichols, 2011;Nichols & Knobe, 2007;Paulhus & Carey, 2011;Pizarro & Helzer, 2010; see also Cushman & Young, 2009).…”
Section: Free Will and Determinismmentioning
confidence: 99%
“…This research has uncovered many exciting results and has shown that people's intuitions about whether free will is possible in a deterministic universe are mixed and vary depending on various contextual and motivational factors (e.g., Clark, Luguri, Ditto, & Knobe, 2014;Deery, Davis, & Carey, 2015;Nadelhoffer, Shepard, Nahmias, Sripada, & Ross, 2014;Nichols, 2011;Nichols & Knobe, 2007;Paulhus & Carey, 2011;Pizarro & Helzer, 2010; see also Cushman & Young, 2009). This research has uncovered many exciting results and has shown that people's intuitions about whether free will is possible in a deterministic universe are mixed and vary depending on various contextual and motivational factors (e.g., Clark, Luguri, Ditto, & Knobe, 2014;Deery, Davis, & Carey, 2015;Nadelhoffer, Shepard, Nahmias, Sripada, & Ross, 2014;Nichols, 2011;Nichols & Knobe, 2007;Paulhus & Carey, 2011;Pizarro & Helzer, 2010; see also Cushman & Young, 2009).…”
Section: Free Will and Determinismmentioning
confidence: 99%
“…They think about the processes that lead them to a particular choice in terms of deliberation and intentionality, see their own actions as internally driven and motivated [69], and come up with internally consistent reasons when the true drivers of choice are not immediately available to them [45]. Even when other people's actions are described as driven by external circumstances, people are still motivated to ascribe intent and responsibility [20].…”
Section: The Need For Autonomy In Consumer Choicementioning
confidence: 99%
“…For instance, belief in free will increases with the desire to hold others morally responsible for their wrongful behaviour and to justify punishment [106]. Similarly, the tendency to condemn others and to see them as morally unreliable is associated with the belief in a moralizing God [107,108].…”
Section: Strategic Moralizing and The Belief In Cosmic Justicementioning
confidence: 99%